Nationalism, Globalization, and Transnational Movement: A Case of Oil Palm Plantation Business in Indonesia - Kano, Hiroyoshi (UI Scholars Hub, 2019)
Since the end of 1957, Dutch enterprises in Indonesia were nationalized and most of palm oil production affiliated with certain corporate groups that are engaged in diversified business. Most of these groups are dominated by ethno-Chinese businessmen. The rapid expansion of oil palm business in Indonesia has induced the inflow of foreign capital to plantation enterprises. The largest inflow has taken place from Singapore. However, most of the investment from Singapore was carried out by business groups dominated by Indonesian Chinese tycoons. This article shows that free-market conditions have influenced the orientation of nationalization of those enterprises. It has created the transnational conglomerate movement in case of palm oil plantation in Indonesia. This article is written based on qualitative research on secondary data from the Center for Statistical Bureau (BPS), etc.